2014
DOI: 10.1007/978-94-017-9612-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Aspects of Microwave Irradiation Practices

Abstract: In the field of organic chemistry, microwave irradiation proved to be a powerful method to enhance chemical processes. In many instances, the use of sealed-vessel high-temperature microwave processing was able to dramatically reduce reaction times, consume less solvent, increase yields, reduce side reactions and improve reproducibility. Microwaves are known to be a more efficient heating method than traditional thermal process where reactions that require long reflux times can sometimes be carried out in a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The effect of MW irradiation on biomass hydrolysis was advantageous mainly by adopting short reaction times and therefore the window of the investigated reaction times was narrow and limited, never exceeding one hour. Temperature represented the main parameter of the process to be optimized, this choice being further supported by the perfect control of this parameter with the MW instrumentation [63]. In order to identify the appropriate reaction temperatures for the FA and LA synthesis, a wide screening of the reaction temperatures was studied, e.g., between 130 and 190 °C and the obtained hydrolyzates were analyzed by GC-MS (see Supplementary Information, Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of MW irradiation on biomass hydrolysis was advantageous mainly by adopting short reaction times and therefore the window of the investigated reaction times was narrow and limited, never exceeding one hour. Temperature represented the main parameter of the process to be optimized, this choice being further supported by the perfect control of this parameter with the MW instrumentation [63]. In order to identify the appropriate reaction temperatures for the FA and LA synthesis, a wide screening of the reaction temperatures was studied, e.g., between 130 and 190 °C and the obtained hydrolyzates were analyzed by GC-MS (see Supplementary Information, Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Gedye et al [ 6 ], the very first group of researchers that related microwave to organic chemistry, observed that the organic reactions could be carried out at a faster rate under microwave irradiation. Since this experiment, the application of microwave irradiation has been reviewed, and they observed that the microwave heating increased the reaction rate, and the formation of side products were reduced compared to the conventional heating method [ 30 ]. These acceleration, reactivity and selectivity changes observed during microwave-assisted reactions enabled energy saving and process intensification, and could be explained through the combination of thermal and non-thermal effects of microwaves.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…According to the 12 principles of green chemistry [1], preparation and development of environmentally-friendly and harmless products and technologies are the main tasks. In this context, the application of the microwave (MW) technique in organic, inorganic, medicinal, analytical and polymer chemistry has spread fast [2][3][4][5][6][7]. Microwave-assisted synthesis is acknowledged as a breakthrough in synthetic chemistry in recent years.…”
Section: Introductionmentioning
confidence: 99%